1995
DOI: 10.1177/106342669500300307
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Competence, Student Diversity, and Staff Training for the Inclusion of Middle School Students with Emotional and Behavioral Disorders

Abstract: The findings from the pilot phase of Project Destiny, a 3-year research and training project concerning the knowledge and skills that middle school teachers need to educate students with emotional and behavioral disorders (EBD) in inclusive settings, are reported. Teachers' self-ratings concerning their knowledge base and skill mastery in the area of EBD were assessed and analyzed. Results of the teacher self-assessments are reported in relation to their ratings of the diverse academic, social, and emotional b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 12 publications
1
24
0
5
Order By: Relevance
“…Responses of Somewhat concerned and Very concerned (vs. Not at all concerned) were collapsed to create a percentage of concern expressed by each group of respondents after discharge. Given survey findings indicating that the overwhelming majority of general and special education teachers do not think that general education teachers have the skills to educate students with emotional and behavioral disorders (Cheney & Barringer, 1995), it is likely that consultation between the RTC staff and the home school personnel may be beneficial to meet the individual needs of the adolescents upon discharge. It should be noted that only RTC staff, not teachers at the residential school, were included in this study, so results may have differed if the educational staff were interviewed.…”
Section: Discussionmentioning
confidence: 99%
“…Responses of Somewhat concerned and Very concerned (vs. Not at all concerned) were collapsed to create a percentage of concern expressed by each group of respondents after discharge. Given survey findings indicating that the overwhelming majority of general and special education teachers do not think that general education teachers have the skills to educate students with emotional and behavioral disorders (Cheney & Barringer, 1995), it is likely that consultation between the RTC staff and the home school personnel may be beneficial to meet the individual needs of the adolescents upon discharge. It should be noted that only RTC staff, not teachers at the residential school, were included in this study, so results may have differed if the educational staff were interviewed.…”
Section: Discussionmentioning
confidence: 99%
“…Cerio (as cited in Vanderbleek 2004) indicated that in school initiated mental health services, family involvement was found to be fundamental in both service utilization and effectiveness. Likewise, a number of studies reported an association between increased caregiver involvement and positive mental health outcomes for adolescents in a variety of programs and settings (Cheney and Barringer 1995;Comer et al 1996;Dishion and Kavanagh 2000;Noser and Bickman 2000;Waugh and Kjos 1992). While promising, an examination of the literature reflects at least four areas of study that need to be targeted in future research.…”
Section: Abstract Caregivers á Serious Emotional Disturbance á Clinicmentioning
confidence: 92%
“…Furthermore, barriers to effective programming in general education settings often include a lack of resources (e.g., special education consultation, paraprofessional support, specialized assessments and planning) and a lack of appropriate training for general education personnel (Cheney & Barringer, 1995;MacMillan, Gresham, & Forness, 1996;Walker & Bullis, 1990). When considered in the context of the increasing demands on general education teachers for academic accountability, it is understandable that there are concerns about retaining students with behavioral disorders in general education rather than simply moving the students to alternative (i.e., special education) classrooms.…”
mentioning
confidence: 98%